2019
DOI: 10.1002/cbic.201900158
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Reversal of Advanced Glycation End Product Modification

Abstract: Advanced glycation end products (AGEs) are a heterogeneous group of molecules that emerge from the condensation of sugars and proteins through the Maillard reaction. Despite a significant number of studies showing strong associations between AGEs and the pathologies of aging‐related illnesses, it has been a challenge to establish AGEs as causal agents primarily due to the lack of tools in reversing AGE modifications at the molecular level. Herein, we show that MnmC, an enzyme involved in a bacterial tRNA‐modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Rational and structure-guided design has also enabled the generation of enzymes for reversing cellular damage adducts, such as advanced glycation end products (AGEs). [19] AGEs are the final products of glycation, the non-enzymatic reaction between nucleophilic groups in biomolecules and reducing sugars or their metabolites. [20] A series of studies link AGEs with age-related conditions and malignant ageing.…”
Section: Dr Freideriki Michailidou Received Her Phd In Chemistry From...mentioning
confidence: 99%
“…Rational and structure-guided design has also enabled the generation of enzymes for reversing cellular damage adducts, such as advanced glycation end products (AGEs). [19] AGEs are the final products of glycation, the non-enzymatic reaction between nucleophilic groups in biomolecules and reducing sugars or their metabolites. [20] A series of studies link AGEs with age-related conditions and malignant ageing.…”
Section: Dr Freideriki Michailidou Received Her Phd In Chemistry From...mentioning
confidence: 99%
“…Thoroughly, their precise mechanisms of action rely on their reactions to carbonyl groups located in the crosslinks between AGEs, subsequently promoting the spontaneous cleavage of carbon–carbon bonds at physiologic pH [ 175 ]. Likewise, an experimental study demonstrated the efficacy of MnmC, an enzyme involved in bacterial tRNA modification, capable of performing a catalytic reversion of the AGEs carboxyethyl-lysine (CEL) and carboxymethyl-lysine (CML) to lysine’s native structure [ 176 ]. The application of these drugs, mainly alagebrium, in diverse animal models has proven to be helpful in arterial stiffness reduction, blood vessel fibrosis [ 173 , 177 ], the development of atherosclerosis [ 178 ], cardiovascular disease [ 179 ], hypertension [ 180 ], and kidney injury [ 181 ].…”
Section: Therapeutic Strategies: Halting the Age–rage Axismentioning
confidence: 99%
“…Moreover, DJ-1 is also capable of converting free MGO into L/D-lactate through intermolecular hydrolysis of DJ-1 arginine and lysine residues that have reacted with the free MGO and formed early glycation intermediates (Toyoda et al, 2014;Zheng et al, 2019). Intriguingly, MnmC, which is involved in the bacterial tRNA-modification pathway and is FAD-dependent, was recently reported to be capable of reversing the AGEs, carboxyethyl-lysine (CEL) and carboxymethyl-lysine (CML), releasing an unmodified lysine structure (Kim et al, 2019). The engineered variant of MnmC has improved catalytic properties against CEL (Fig.…”
Section: Regulatory Mechanisms Of Glycationmentioning
confidence: 99%
“…The engineered variant of MnmC has improved catalytic properties against CEL (Fig. 4E), thus providing insights into future protein-based therapies for AGE-induced protein damage (Kim et al, 2019).…”
Section: Regulatory Mechanisms Of Glycationmentioning
confidence: 99%